Analisis Faktor-Faktor yang Memengaruhi Ketahanan UMKM Makanan dan Minuman Bersertifikat Halal saat Pandemi COVID-19 di Kota Banda Aceh - Wahyu Viariani; Deni Lubis; Marhamah Muthohharoh (Department of Islamic Economics, IPB University, 2022)
The existence of the COVID-19 pandemic has implications for the global economic sector, including in Indonesia. The decline in economic performance is not only felt by large multinational and national companies, but also by MSME players. This research aims to examine the factors of resilience of MSMEs during the COVID-19 pandemic, so that the results of this research can be a survival strategy for MSMEs, especially during the pandemic. The research data was collected through an interview process with 100 food and beverage MSME actors who have halal certification and who do not have halal certification in Banda Aceh City. After that, MSMEs will be grouped into MSMEs that have resilience and do not have resilience for further analysis. The analysis method used in this research is descriptive analysis and logistic regression analysis. Based on the research results, the factors that positively and significantly affect the resilience of MSMEs during the COVID-19 pandemic are the characteristics of entrepreneurship and government support.